TANGGUNG JAWAB PARA PIHAK DALAM PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR TERMINAL KIJING PONTIANAK - Nawang Calistya Sari,; Taupiqqurrahman, (JURNAL HUKUM DAN KENOTARIATAN, 2022)
Equitable development in all regions of Indonesia through the National Strategic Program is one of the government's efforts to improve facilities and infrastructure to support the development of various fields. One of the National Strategic Programs is Kijing Terminal in West Kalimantan. The parties in the construction of the Kijing Terminal are Pelindo II (Persero) as the service user and PT Wijaya Karya (Persero) Tbk. as a service provider. In carrying out the contractual relationship between the two parties, it is regulated in an agreement agreed upon by both parties. However, in the agreement, there are problems, namely the termination of work by fishing communities and landowners related to the land acquisition that has not been resolved by the service users, thus harming the service providers both in terms of time, equipment rental costs, and workers in the construction of Kijing Terminal. This research uses descriptive normative legal research. Data collection was obtained through literature study and document study. Data analysis was carried out in a qualitative descriptive manner. It is necessary to further study the legal responsibilities of the parties in the construction implementation agreement among PT Pelabuhan Indonesia II (Persero) and PT Wijaya Karya (Persero) Tbk. in the implementation of the construction of the Kijing Terminal and the efforts that must be made for the late payment of land compensation by service users in the agreement for the construction work of the West Kalimantan Kijing Terminal. PT Pelindo II should have completed the land acquisition process before the construction of the Kijing Terminal by PT Wijaya Karya, then PT Wijaya Karya should ensure that the land acquisition for the construction of the Kijing terminal has been completed, and should have completed the land acquisition by the agreed contract after signing the contract.